Report of the Working Group on Empowering the Other Backward Classes for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
One of the mechanisms adopted by the Planning Commission for the formulation of Five Year Plans, is the setting up of Working Groups for each sector. Their Members consist not only of representatives of Ministries and State Governments but also individuals with expertise and experience in and knowledge of the relevant area. In the sector pertaining to weaker sections or weaker social categories, the first Working Groups for Scheduled Castes and Scheduled Tribes was set up during the run-up to the formulation of the Medium-term Plan in 1977-78.
Government of India, Planning Commission